Impact of Treat-to-Target Therapy on Bone Mineral Density Loss in Patients With Rheumatoid Arthritis: A Prospective Cohort Study - Huang, Hong; Wang, Yu; Xie, Wenhui; Geng, Yan; Gao, Dai; Zhang, Zhuoli (Frontiers in Endocrinology, 2022)
Background: Osteoporosis is a common comorbidity of rheumatoid arthritis (RA). Although RA disease activity has been demonstrated to be associated with bone loss in previous studies, most of them were cross-sectional studies and not in the context of treat-to-target (T2T) strategies. Objectives: To evaluate the association of disease activity with bone mineral density (BMD) changes in the context of T2T strategies in a prospective RA cohort. Methods: RA patients were enrolled from a prospective CENTRA cohort of Peking University First Hospital. The follow-ups have been scheduled every 3 to 6 months. BMD was repeated at baseline, 1-year and then every other year. Demographics, baseline clinical features, laboratory data, and medications at each visit were recorded. Time-adjusted mean disease activity scores were adopted to reflect the overall disease activity during follow-up. The influence of univariable associations between predictors and BMD was investigated using linear regression Results: A total of 268 patients were included in our analysis. Their mean age was 50 (12.9) years and 224 (83.6%) were women. The median (IQR) disease duration was 48.7 (107.6) months. Osteoporosis at lumbar spine was observed in 23.1% patients and 9.3% at femoral neck at enrollment. Older age, higher SDAI score and lower BMI were found to be associated with osteoporosis at baseline. The proportion of patients achieved DAS28-ESR, CDAI and SDAI remission or LDA at the end of first year was 71.5%, 68.8% and 67.4%. Reevaluations of BMD at 1 year was applied in 144 patients. Mean decreases of BMDs were 1.75 % at the lumbar spine and 1.40 % at femoral neck at 1 year form baseline, respectively. Patients who achieved remission had less yearly bone loss at lumbar spine (p=0.036). Female gender was identified as a risk factor in the multiple linear regression analyses, and lower disease activity and bisphosphonates were protective factors of continuous bone loss. Conclusion: Disease activity is associated with bone loss in RA patients in the context of T2T strategies, and those who achieved remission had less yearly bone loss.